Management Accountant’s Role and Functions in the Enterprise Resource Planning Environment – Author’s Own Research into Enterprises in Poland - Zarzycka, Ewelina (Comparative Economic Research. Central and Eastern Europe, 2012)
ERP systems have revolutionized practically all aspects of business processes in enterprises. They help improve the processes by ensuring their integration. Ensuring integration between financial and non-financial data, an ERP package gives new quality to the management of enterprise value. All these features make ERPs particularly important for specialists responsible for providing management information and measuring performance of the company. This article seeks to answer whether the implementation of an ERP system has an effect on the management accountant’s tasks and functions, especially in the field of performance measurement and internal reporting. The ERP impacts on the controller’s role in the organization will be evaluated using field studies on six enterprises owned by multinational corporations. The question that should be asked here is whether controller’s functions and tasks will also be unaffected.